Case report: Side effects of etomidate in propylene glycol in five Göttingen Minipigs - Petrucci, Mariafrancesca; de Brot, Simone; Casoni, Daniela (Frontiers in Veterinary Science, 2024)
Etomidate, an agonist of the GABA A receptors, is available for clinical use either in combination with 35% propylene glycol or in lipid emulsion. Its recognized ability to minimally impact the cardiovascular system made etomidate a suitable option for cardiac compromised patients. Myoclonus and pain at injection are recognized side effects of etomidate in propylene glycol in human and veterinary species. No information is available in minipigs. In the present case series, we wanted to report side effects related to the use of etomidate in 35% propylene glycol in five Ellegaard Göttingen Minipigs, who underwent general anesthesia for cardiac magnetic resonance imaging, days or weeks after experimentally induced myocardial infarction. Following intravenous injection of etomidate, laryngeal edema and hyperemia were observed in one case. In another case, tachycardia, apnea, and decreased oxygen saturation, accompanied by laryngeal edema and hyperemia were observed, which resolved spontaneously in few minutes. In the arterial or venous samples collected shortly after induction of general anesthesia, hemolysis was macroscopically visible and subsequently confirmed with hematological exam in all the five cases, as well as hemoglobinuria. Necropsies carried out immediately after euthanasia confirmed macroscopic laryngeal edema (1 animal), severe laryngeal edema and marked diffuse lung alveolar and interstitial edema and congestion at histology (1 animal) and marked acute lung congestion (1 animal). These side effects were not observed when etomidate in lipid emulsion was injected in further 24 animals. The role played by the different formulations (propylene glycol versus lipidic formulation) has not been yet fully elucidated. Based on our observations, we recommend caution in using the formulation of etomidate in 35% propylene glycol in Göttingen Minipigs.